Identification of a Mutation in the Novel Compound Heterozygous CFTR in a Chinese Family with Cystic Fibrosis. (7th May 2020) - Shao, Hongxia; Hua, Jingna; Wu, Qi; Li, Xiaoge; Zhang, Ming; Wang, Herong; Wu, Junping; Xu, Long; Xie, Yi; Li, Li; Chen, Huaiyong
Abstract : Cystic fibrosis (CF) is one of the most common autosomal recessive disorders among Caucasians of Northern European descent but is uncommon in the Chinese population. Objectives . To elucidate the mutation in the novel compound heterozygous CFTR causing CF in Chinese family. Materials and Methods . Clinical samples were obtained from a Chinese family, the brother and sister with recurrent airway infections, hypoxemia and obstructive ventilatory impairment, sinusitis, clubbed fingers, salty sweat, and nasal polyposis. We performed whole-exome sequencing on the family and validated all potential variants by Sanger sequencing. Results . Next-generation sequencing showed a novel compound heterozygous CFTR mutation (c.400 A > G p.Arg134Gly and c.3484 C > T p.Arg1162 ∗ ) which resulted in CF in the family. Conclusions . As this mutation is consistent with the observed clinical manifestations of CF and no other mutations were detected after scanning the gene sequence, we suggest that their CF phenotypes are caused by the compound heterozygous mutation, c.400 A > G p.Arg134Gly and c.3484 C > T p.Arg1162 ∗ . As c.400 A > G is not currently listed in the Cystic Fibrosis Mutation Database, this information, regarding the CF-causing mutations in two Chinese patients, is of interest.